Dynamic state estimation of multi-machine power system with UPFC using EKF algorithm - Meera R Karamta; Jitendra G Jamnani (Indonesian Journal of Electrical Engineering and Computer Science, 2021)
Estimation of dynamic state variables in a multi-machine power system connected with UPFC is presented in this paper, using Extended Kalman filter (EKF) algorithm. A two-generator test case is used to estimate the generator rotor angle and rotor speed. The DC link voltage of the UPFC is the additional state variable to be estimated. Dynamic mathematical modeling of the multi-machine system with UPFC is explained in this work. DSE is done under transient condition of three-phase fault.